2006
DOI: 10.1007/s00208-006-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Abelian subvarieties of Drinfeld Jacobians and congruences modulo the characteristic

Abstract: Abstract.We prove a level lowering result over rational function fields, with the congruence prime being the characteristic of the field. We apply this result to show that semi-stable optimal elliptic curves are not Frobenius conjugates of other curves defined over the same field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…If n is irreducible, this is [Pa1, Theorem 1.2]. More generally, in the terminology of[Pa2], if E is not Frobenius minimal, then by [Pa2, Theorem 1.1] we have p ∈ C (p), but C (p) = ∅ since S(n) p-old = 0. 2…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…If n is irreducible, this is [Pa1, Theorem 1.2]. More generally, in the terminology of[Pa2], if E is not Frobenius minimal, then by [Pa2, Theorem 1.1] we have p ∈ C (p), but C (p) = ∅ since S(n) p-old = 0. 2…”
mentioning
confidence: 90%
“…More precisely, they are obtained from finitely many curves by repeated application of the Frobenius isogeny. Papikian [Pa1,Pa2] has shown that in certain situations the strong Weil curve is not the Frobenius of another curve over F q (T ), but from examples it is known that this is not a general phenomenon.…”
mentioning
confidence: 92%